Responses of plasma concentrations of A type natriuretic peptide and B type natriuretic peptide to alacepril, an angiotensin-converting enzyme inhibitor, in patients with congestive heart failure. Issue 6 (December 1994) - Yoshimura, M; Yasue, H; Tanaka, H; Kikuta, K; Sumida, H; Kato, H; Jougasaki, M; Nakao, K
Abstract : BACKGROUND--Plasma concentrations of A type or atrial natriuretic peptide (ANP) and B type or brain natriuretic peptide (BNP) are increased in patients with congestive heart failure (CHF). OBJECTIVE--To examine the haemodynamic and hormonal responses, especially of ANP and BNP, to oral administration of an angiotensin-converting enzyme (ACE) inhibitor in patients with CHF and in controls. PATIENTS--12 patients with CHF and 11 controls. METHODS--Haemodynamic variables and plasma concentrations of ANP, BNP, and other hormones were serially measured for 24 hours after alacepril (37.5 mg) was given by mouth. RESULTS--Pulmonary capillary wedge pressure and systemic vascular resistance decreased significantly in both groups. The cardiac index increased only in the CHF group. In patients with CHF pulmonary capillary wedge pressure, systemic vascular resistance, and cardiac index were significantly changed from 1 to 12 hours after alacepril administration. Plasma ANP and BNP decreased significantly after alacepril was given to the CHF group: neither concentration changed in the control group. In the CHF group plasma ANP was significantly lower between 1 and 6 hours and was highly significantly correlated with pulmonary capillary wedge pressure. Plasma BNP, however, was significantly lower between 6 and 24 hours after alacepril and was not correlated with pulmonary capillary wedge pressure. CONCLUSIONS--The response of plasma BNP after alacepril administration occurred later and lasted longer than the plasma ANP response. This may indicate that the mechanisms of synthesis, secretion, or degradation of the two peptides are different.